Comparison between AMH level in Multipara and Nullipara in Women More than 40 Years Old - Hanan Khudheir Hussein1, Adnan AH Albdairi2, Rana T Mehsen3, Zahra K Hussein4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Decreased ovarian reserve is considered as one of the main causes of infertility. It is about the availability of preovulatory oocytes in the ovaries. With increase age, ovarian reserve decreases. Nowadays, “ovarian reserve” assessment became a strategy to assess female infertility.Objective: The current study aims to find the relationship between age and infertility type with measures of ovarian reserve (FSH, AMH and AFC) in infertile patients.Material and Method: The cross-sectional study design was used for this study and a survey was conducted among 100 infertile women.Result: Results revealed that Relationships between age and ovarian reserve indicators show a highly significant negative correlation with AFC (p= 0.001) and AMH (p= 0.007) level while positive correlation is found with FSH level (p= 0.001). The relation between age and FSH was moderate (rs=0.38, p<0.0001) and revealed that AMH and AFC level decreases while FSH level increases with age.Conclusion Study of AMH level is the most reliable source to measure age-specific changes.